The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.14814/phy2.13580
|View full text |Cite
|
Sign up to set email alerts
|

The relation between maximal voluntary force in m. palmaris longus and the temporal and spatial summation of muscle fiber recruitment in human subjects

Abstract: This study aimed at looking at the frequency (T‐score) and the amplitude (S‐score) of fiber use during contraction of a forearm muscle, m. palmaris longus, as measured by acoustic myography (AMG). An additional aim was to relate the T‐ and S‐scores to the recorded force obtained from a hand dynamometer. The hypothesis being that temporal and spatial summation of muscle fiber contraction in a given muscle during a given movement, can together describe a given obtained force. Force measurements were carried out … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
18
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(26 citation statements)
references
References 15 publications
5
18
0
Order By: Relevance
“…The data from the healthy AMG study [9] confirmed an earlier pilot study showing that muscle fibre recruitment (temporal and spatial summation) for a given type of force production is similar in men and women [11]. The study showed that the force produced by m. palmaris longus, although weaker for women than for men, was regulated identically for both genders and was closely correlated with the recorded AMG signal for this muscle [11]. The method applied in this study had the advantage over similar yet earlier methods, such as those used by Stokes and Blythe [12] and Madeleine [13], in that the sensors had a vastly improved frequency response, thereby providing a true image of muscle fibre use.…”
Section: Introductionsupporting
confidence: 78%
See 2 more Smart Citations
“…The data from the healthy AMG study [9] confirmed an earlier pilot study showing that muscle fibre recruitment (temporal and spatial summation) for a given type of force production is similar in men and women [11]. The study showed that the force produced by m. palmaris longus, although weaker for women than for men, was regulated identically for both genders and was closely correlated with the recorded AMG signal for this muscle [11]. The method applied in this study had the advantage over similar yet earlier methods, such as those used by Stokes and Blythe [12] and Madeleine [13], in that the sensors had a vastly improved frequency response, thereby providing a true image of muscle fibre use.…”
Section: Introductionsupporting
confidence: 78%
“…The method differs from surface electromyography (sEMG), since it measures the pressure waves generated by activated muscles rather than their electrical depolarization, thus avoiding the influence of neuromuscular endplates, which confound the sEMG signal [10]. The data from the healthy AMG study [9] confirmed an earlier pilot study showing that muscle fibre recruitment (temporal and spatial summation) for a given type of force production is similar in men and women [11]. The study showed that the force produced by m. palmaris longus, although weaker for women than for men, was regulated identically for both genders and was closely correlated with the recorded AMG signal for this muscle [11].…”
Section: Introductionsupporting
confidence: 66%
See 1 more Smart Citation
“…Acoustic myography (AMG) is a biomechanical method measuring generated pressure waves from a contracting muscle [9] [10]. AMG recordings were carried out with a CURO unit and CURO sensors (CURO-Diagnostics ApS, Denmark; formerly MyoDynamikApS) and followed in real time on an iPADAir (Apple Inc., Cupertino, CA, USA) via the App "CURO Clinic" and a specialized data recording system.…”
Section: Recordingsmentioning
confidence: 99%
“…Recorded data was stored to the CURO Unit and after completion of measurements transferred to the CURO software (https://app.myodynamik.com). The ESTi-score with its three components: 1) efficiency (E-score) 2) temporal fibre recruitment (T-score) and 3) spatial fibre recruitment (S-score), was calculated using the company software [9] [10].…”
Section: Recordingsmentioning
confidence: 99%